ANALISIS POSTUR KERJA DENGAN TINJAUAN ERGONOMI DI INDUSTRI BATIK MADURA - Fitri Agustina; Arief Maulana (UII, 2012)
Macajah village is the name of one of the villages in the district Tanjungbumi, Bangkalan district. Macajah batik which has good quality and fineworkmanship that has reached millions of Rupiahs selling price. In the village Macajah batik - making process is still done simply. Therefore grievances felt operator when working must be considered, and it was due to lack of ergonomic posture of the operator when working. The purpose of this research is to improve the working methods of the small industrial facilities batik designs with improve demployment and good working posture solutions for operators. The method used in this study is the method of RULA (Rapid Upper Limb Assessment) is a method that investigates complaints of harassment and human upper body. With the posture of the operator will evaluate the extent to which level action should be taken. The results showed a decrease in the risk level from medium to smaller level after the simulated repair work posture and use of new work on the operator. Keywords: working posture, RULA (Rapid upper limb assessment)